Penggunaan Presuposisi Eksistensial dalam Kolom Komentar Instagram @jakarta.keras pada Unggahan Kasus Korupsi PT Pertamina Patra Niaga - Vivit Arista Dewi; I Wayan Pastika; I Wayan Simpen (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2026)
This study aims to describe the use of existential presupposition in the comment section of the Instagram account @jakarta.keras on a post concerning the corruption case of PT Pertamina Patra Niaga dated February 25, 2025. This research employs a qualitative descriptive approach from a pragmatic perspective. The data consist of utterances in the comment section that contain assumptions regarding the existence of particular entities. Data were collected using the observational method with the non-participatory observation technique, while data analysis was conducted using the pragmatic equivalent method through the Determining Element Sorting (Pilah Unsur Penentu/PUP) technique. The results indicate that existential presuppositions appear in various forms, which are classified into four categories: individual-based, group-based, social status–based, and ownership-relation–based existential presuppositions. These presuppositions are constructed through the use of definite noun phrases, proper names, plural forms, social status markers, and possessive markers. The findings demonstrate that Instagram comment sections function not only as a medium for expressing opinions but also as a space for constructing assumptions about the existence, identity, and social relations of actors involved in an event.